2022
DOI: 10.21203/rs.3.rs-2249886/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of blood total immunoglobulin E and eosinophils with radiological features of bronchiectasis

Abstract: Background: Our study aimed to investigate whether serum total IgE and blood eosinophils, were associated with radiological features of bronchiectasis in a Chinese cohort. Methods: We retrospectively enrolled bronchiectasis patients who visited Peking University Third Hospital from Jan 1st, 2012 to Oct 7th, 2021. The clinical, laboratory and chest CT characteristics were analyzed in association with serum total IgE level and blood eosinophil count. Results: A total of 125 bronchiectasis patients were enrolled,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…We found that the serum T-IgE data was not normally distributed (statistical K-S = 0.286, P < .01), thus the serum T-IgE was converted using logarithmic transformation method. [11] The logarithmically transformed T-IgE (ln-T-IgE) values were in accordance with normal distribution (statistical K-S = 0.040, P = .200). Among all patients, 49.82% patients exhibited elevated T-IgE levels.…”
Section: Resultsmentioning
confidence: 78%
“…We found that the serum T-IgE data was not normally distributed (statistical K-S = 0.286, P < .01), thus the serum T-IgE was converted using logarithmic transformation method. [11] The logarithmically transformed T-IgE (ln-T-IgE) values were in accordance with normal distribution (statistical K-S = 0.040, P = .200). Among all patients, 49.82% patients exhibited elevated T-IgE levels.…”
Section: Resultsmentioning
confidence: 78%